Magnetically induced transparency of a quantum metamaterial composed of twin flux qubits - K. V. Shulga (Nature Portfolio, 2018)
Here, the authors demonstrate an array of superconducting qubits embedded into a microwave transmission line. They show that the transmission through the metamaterial periodically depends on externally applied magnetic field and suppression of the transmission is achieved through field-induced transitions.